Program Pembinaan Life Skill Santri Berbasis Pendidikan Islam untuk Meningkatkan Kemandirian di MA Sa'id Yusuf - Nadiya, Siti Aisyatun; Safitri, Nadiya; Maharani, Sintya Ayu; Fajriana, Rustam (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2026)
This Devotion Activity describes the effort to develop the life skills of students at MA Sa'id Yusuf through an Islamic education approach that is integrated with the pesantren system. In the context of MA Sa'id Yusuf's problem, this institution tries to form the independent character of students while preparing them with relevant skills for everyday life. The purpose of this activity is to explore and deepen the influence of Islamic education in strengthening students' life skills and their independent character. The method used in this research is a qualitative descriptive approach, with data collection through direct observation during the Field Experience Program (PPL). This research focuses on students' daily activities, the learning process, and the application of Islamic values ​​in the pesantren environment. The results of the activity show that the development of students' life skills is done through worship, study discipline, responsibility for daily tasks, cooperation, and examples from teachers and seniors. These activities contribute to the formation of students' independent character, especially in time management, personal responsibility, and independence in daily activities. However, in order to optimize the development of these life skills, there is a need for further strengthening of the practical skills program. This will help students not only in the academic aspect but also in their preparation to face challenges in the outside world. Thus, Islamic education at MA Sa'id Yusuf does not only focus on religious knowledge, but also on the development of character and skills needed to become an independent and responsible individual